PENGARUH PENGHARGAAN FINANSIAL, PROMOSI JABATAN, DAN KEPUASAN KERJA TERHADAP KINERJA KARYAWAN YANG DIMEDIASI OLEH LOYALITAS KARYAWAN (STUDI EMPIRIS: KARYAWAN PT XXX JAKARTA) - Eka Ardyah Garini; Andreas Heryjanto (Faculty of Economics and Business | Universitas Diponegoro, 2021)
The purpose of this study was to find out the effect of financial rewards, promotions, and job satisfaction on employee performance mediated by employee loyalty, where an empirical study was conducted on employees of PT XXX. In this research, hypothesis testing is used and this type of research is included in quantitative research. Primary data in this study were obtained by distributing questionnaires as many as 224 valid questionnaires given to respondents who were employees of PT XXX. Sampling with proportional stratified random sampling technique. Data analysis was processed using Structural Equation Model (SEM) with Smart PLS software version 3.2. The results were found if financial rewards have a positive and significant effect on employee performance, promotion has a positive and significant effect on employee performance, and job satisfaction has a positive and significant effect on employee performance. Then financial rewards have a positive and significant effect on employee loyalty, but promotion does not have a positive and significant effect on employee loyalty, and job satisfaction has a positive and significant effect on employee loyalty. Then employee loyalty has a positive and significant effect on employee performance, financial rewards have a positive and significant impact on employee performance mediated by employee loyalty. However, job promotion does not have a positive and significant effect on employee performance mediated by employee loyalty, and job satisfaction has a positive and significant effect on employee performance mediated by employee loyalty. The limitation in this study lies in the use of samples, which were only obtained from one private hospital in North Jakarta. Therefore, the results in this study cannot be generalized to all hospitals, because of the different characteristics between hospitals.